Philosophical values in number theory of Ikhwān Al-Ṣafā' - Al Walid, Kholid; Miri, Mohsen; Rijal, Syamsul; Lestari, Ayu; Norman, Nurul Ain (UIN Ar-Raniry Banda Aceh, Aceh, 2024)
In mathematics, especially in the Arithmetic section, there is number theory which can represent theological values. Mathematics is often presented with materialist values without deep meaning. One group of classical philosophers who have mathematical thinking, especially number theory, which not only explains the material of numbers themselves, but also links it to meaningful theological values is the Ikhwān al-Ṣafā'. This research aims to reveal the theological values contained in the thinking about numbers. Using the literature study method, the researcher specifically studied the phenomenal book Rasā'il Ikhwān al-Ṣafā' as the primary source. Researchers found that in the Ikhwān al-Ṣafā' number theory, there is the value of monotheism which is described by the characteristics of the number one and the value of creation which is described by the ladder of numbers.